PENGARUH COORPORATE SOCIAL RESPONSIBILITY PADA HUBUNGAN FAKTOR - FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Endiana I Dewa Made (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
The essence of a business activity is to provide the maximum possible benefit to owners or shareholders. The increase of stock price means the higher value of the company so that the welfare of shareholders will be increased as well. The value of the company also reflects the performance of management in the company’s operations. There are several factors that can affect the value of companies such as profitability, dividend policy, debt policy and Corporate Social Responsibility (CSR). The problem in this research are how effect of profitability, dividend policy and debt policy to the value of the company and also whether CSR is able to affect the relationship of profitability, dividend policy and debt policy. The expected value obtained from this study is to determine the factors that may affect the value of the company and to determine whether CSR may affect the relationship between factors that affect the value of the company.The population in this research is manufacturing company in Indonesia Stock Exchange 2012-2014 period with purposive sampling method in order to obtain as many as 62 companies. The analysis technique used is moderated regression analysis.The results showed, the positive effect on the profitability of the company’s value, dividend policy positive effect on the value of the company, the debt policy has no effect on the value of the company. The test results showed that CSR moderation capable of affecting relations on the value of the company’s profitability, CSR is not capable of affecting relations on the value of the company’s dividend policy and CSR are not able to affect relations with the company’s debt policy. The results of this study are expected to be one of the considerations by the investor in making an investment in the capital market which is expected not wrong in choosing the company as a place for investment, because in fact the investors expect a return on their investments.